Massive hemorrhage arising of inferior thyroid artery by radiofrequency ablation for secondary hyperparathyroidism: Two case reports. Issue 49 (9th December 2022) - Liu, Xiaoling; Qin, Xiachuan; Hu, Xiaomin; Wang, Zhihua
Abstract : Patient concerns and diagnosis: Secondary hyperparathyroidism (SHPT) is a common complication of chronic kidney disease. Radiofrequency ablation (RFA) is a safe and minimally invasive treatment for SHPT, which can effectively reduce the level of parathyroid hormone (PTH). Inferior thyroid artery (ITA) is a rare and dangerous complication, We report two cases of ITA bleeding caused by RFA. Intraoperative contrast-enhanced ultrasound (CEUS) can accurately show the source and scope of bleeding. Ultrasound guided RFA and compression hemostasis were successful. Interventions: During the operation, CEUS was used to detect ITA bleeding, bleeding range and location quickly and accurately at the early stage, and ultrasound guided compression and RFA were used to treat small bleeding points. ITA bleeding was timely and effectively controlled, and the bleeding range was limited to pseudoaneurysm. Outcomes: The patient received antiplatelet and anticoagulant therapy for 2 days, and the pseudoaneurysm was filled with thrombus 36 hours and 72 hours after surgery. Later, the ultrasonography examination showed that the hematoma was gradually absorbed and contracted. Conclusion: Although RFA is a safe and minimally invasive treatment for secondary hyperparathyroidism, rupture and bleeding of the ITA are rare and dangerous. CEUS can quickly and accurately judge bleeding, bleeding range and location in the early stage. Ultrasound guided compression and RFA of small ITA bleeding points can timely and effectively control bleeding, limit the bleeding range to pseudoaneurysms, and close themselves.